Penerapan Terapi Akupresure Terhadap Penurunan Nyeri Kepala Pada Penderita Hipertensi Melalui Aplikasi Teori Jean Watson Di Puskesmas Lingkar Timur Kota Bengkulu - Windiah, Nola; Hermiati, Dilfera (Jurnal Pakar Kesehatan, 2025)
Hypertension is a condition in which systolic blood pressure exceeds 120 mmHg and diastolic pressure exceeds 80 mmHg. The purpose of this study is to apply acupressure therapy to ruduce headaches in hypertensive partients through the application of Jean Watson’s theory at the Lingkar Timur Community Health Center Bengkulu City in 2025.